Cesarean Delivery in a Parturient with Left Ventricular Noncompaction Complicated by Acute Pulmonary Hypertension After Methylergonovine Administration for Postpartum Hemorrhage. (15th June 2015) - Spitzer, Yelena; Weiner, Menachem M.; Beilin, Yaakov
Abstract : Left ventricular noncompaction is a rare congenital cardiomyopathy that is an arrest in the normal process of cardiac compaction, resulting in the development of multiple prominent trabeculations in the left ventricle. We report a case of a parturient with left ventricular noncompaction causing decompensated heart failure who underwent cesarean delivery that was complicated by an acute pulmonary hypertensive crisis.